2020
DOI: 10.1002/ijfe.1826
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the volatility of crude oil returns: Jumps and volatility forecasts

Abstract: We contribute to the scarce literature on the oil market volatility index (OVX) by examining the presence of time‐varying jumps in OVX and by assessing the ability of OVX to predict the conditional variance of crude oil returns. Using a GARCH‐jump model, we find evidence that OVX is characterized by jump behaviour that tends to vary over time. Further analysis indicates that accounting for the jump behaviour of OVX helps improve the conditional variance forecasts of crude oil returns. Since the studied feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 54 publications
(72 reference statements)
7
21
0
Order By: Relevance
“…Our results are in line with those of (Aït-Sahalia 2004;Amaya and Vasquez 2011;Apergis and Apergis 2020;Baker et al 2020;Dutta et al 2020;Eraker et al 2003 2020) conducted a study on the Chinese stock market, an emerging market, and emerging markets are mostly speculative due to the availability of a limited number of shares for trading in stock markets and the increasing role of institutional investors who act as noise traders. Therefore, they expected more jumps to occur in emerging markets.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are in line with those of (Aït-Sahalia 2004;Amaya and Vasquez 2011;Apergis and Apergis 2020;Baker et al 2020;Dutta et al 2020;Eraker et al 2003 2020) conducted a study on the Chinese stock market, an emerging market, and emerging markets are mostly speculative due to the availability of a limited number of shares for trading in stock markets and the increasing role of institutional investors who act as noise traders. Therefore, they expected more jumps to occur in emerging markets.…”
Section: Discussionsupporting
confidence: 88%
“…Amaya and Vasquez (2011) suggest that positive jumps raise the prices of securities; therefore a risk-averse investor prefers positive jumps over a negative jump. Dutta et al (2020) suggested including jumps to developed a more reliable model for volatility and for asset pricing. We also found that jumps play a crucial role in asset returns.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Normandin and Phaneuf (2004) and Caporale et al (2017) presented that time-varying conditional volatility commonly exists in financial assets’ returns. Daal et al (2007) and Kuttu (2017) , and Dutta et al (2020) found that conditional jumps of equity returns change over time. Engle and Lee (1999) also characterized permanent and transitory components beyond the conditional variance of equity returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Kho (1996) , Fong and See (2002) , Normandin and Phaneuf (2004) , and Caporale et al (2017) demonstrated that time-varying conditional volatility is a typical feature of financial asset and derivative returns. Daal et al (2007) and Kuttu (2017) , Bégin et al (2020) , and Dutta et al (2021) found that conditional jump risk matters when pricing equity values. Engle and Lee (1999) , Adrian and Rosenberg (2008) , and Liu (2021) characterized permanent and transitory components for evaluating the volatility of an equity's returns and demonstrated that the model incorporating these two components outperforms other models.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%